Renewed proliferation in adult mouse cochlea and regeneration of hair cells - Yilai Shu; Wenyan Li; Mingqian Huang; Yi-Zhou Quan; Deborah Scheffer; Chunjie Tian; Yong Tao; Xuezhong Liu; Konrad Hochedlinger; Artur A. Indzhykulian; Zhengmin Wang; Huawei Li; et al. (Nature Communications, 2019)
The adult mammalian inner ear cells cannot regenerate nor proliferate. Here, the authors show that co-activation of Myc and NOTCH pathways can stimulate proliferation of inner ear sensory epithelial cells, which can be induced to become hair cell-like cells in vitro and in vivo.